Female reproductive functions of the neuropeptide PACAP - Miklos Koppan; Zsuzsanna Nagy; Inez Bosnyak; Dora Reglodi (Frontiers in Endocrinology, 2022)
Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuropeptide originally isolated as a hypothalamic peptide. It has a widespread distribution in the body and has a diverse spectrum of actions. Among other processes, PACAP has been shown to be involved in reproduction. In this review we summarize findings related to the entire spectrum of female reproduction. PACAP is a regulatory factor in gonadal hormone production, influences follicular development and plays a role in fertilization and embryonic/placental development. Furthermore, PACAP is involved in hormonal changes during and after birth and affects maternal behavior. Although most data come from cell cultures and animal experiments, increasing number of evidence suggests that similar effects of PACAP can be found in humans. Among other instances, PACAP levels show changes in the serum during pregnancy and birth. PACAP is also present in the human follicular and amniotic fluids and in the milk. Levels of PACAP in follicular fluid correlate with the number of retrieved oocytes in hyperstimulated women. Human milk contains very high levels of PACAP compared to plasma levels, with colostrum showing the highest concentration, remaining steady thereafter for the first 7 months of lactation. All these data imply that PACAP has important functions in reproduction both under physiological and pathological conditions.